FRI0033 Important role of CD11C+ dendritic cells in inflammatory arthritis. (15th June 2017) - Puchner, A; Saferding, V; Bonelli, M; Leiss, H; Pfeifle, R; Kroenke, G; Koenders, M; Smolen, J; Redlich, K; Blüml, S
Abstract : Background: Dendritic cells (DCs) are important antigen presenting cells (APCs) and therefore they play an important role in bridging the innate and the adaptive immune response. DCs can be divided in different subsets with specific functions. As powerful APCs, DCs are thought to play an important role in the induction of autoimmune diseases such as rheumatoid arthritis. However, the active role of DCs in joint inflammation is not known yet. Methods: We analyzed histological sections of K/BxN serum transfer arthritis as well as hTNFtg arthritis for the presence of CD11c + cells by immunohistochemistry. We also performed synovial biopsies and analyzed the cellular composition of the inflammatory infiltrate with respect to DCs. We used CD11c-diphteria toxin receptor (DTR) transgenic mice, which express the human diphtheria-toxin receptor under the CD11c promoter, allowing for specific depletion of CD11c + cells by administration of diphtheria toxin (DT). K/BxN serum transfer arthritis was induced, and mice were given either DT or PBS or in wt and BARF3 deficient mice. In addition CD11c DTR mice were crossed into hTNFtg animals and also received either DT or PBS. The severity of arthritis was determined clinically and histologically. Results: We show that Cd11c + cells are present in significant numbers in the synovia of K/BxN and TNF driven arthritis. Both CD8 + CD11c + and CD11b + CD11c +, can be found in synovial tissue. Upon depletion of CD11c+ cells clinical signs of K/BxN serum transfer arthritis were significantly reduced. Histological analysis found reduced synovial inflammation after the depletion of CD11c + cells in K/BxN arthritis. In addition, local bone destruction and the number of osteoclasts was also significantly reduced. Analysis of K/BxN arthritis in wt mice and BATF3 -/- mice, which lack a subset of DCs, namely CD8 + CD11 + DCs, revealed no difference in arthritis severity between the two groups. In addition to K/BxN arthritis, we found that also in TNF-driven arthritis depletion of CD11c + cells led to a striking reduction of synovial inflammation and a complete depletion of osteoclasts. Conclusions: These data show that in addition to initiating an adaptive immune response, CD11c + dendritic cells, are also involved in innate effector mechanisms of inflammatory arthritis. Especially CD11b + CD11c + and monocyte derived inflammatory seem to play a role in inflammatory arthritis, suggesting that they could be an important therapeutic target for patients suffering from inflammatory arthritis. Disclosure of Interest: None declared